Structures and Functions of the 3′ Untranslated Regions of Positive-Sense Single-Stranded RNA Viruses Infecting Humans and Animals - Liu, Yuanzhi; Zhang, Yu; Wang, Mingshu; Cheng, Anchun; Yang, Qiao; Wu, Ying; Jia, Renyong; Liu, Mafeng; Zhu, Dekang; Chen, Shun; Zhang, Shaqiu; Zhao, XinXin; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The 3’ untranslated region (3’ UTR) of positive-sense single-stranded RNA (ssRNA(+)) viruses is highly structured. Multiple elements in the region interact with other nucleotides and proteins of viral and cellular origin to regulate various aspects of the virus life cycle such as replication, translation and the host-cell response. This review attempts to summarize the primary and higher order structures identified in the 3’UTR of ssRNA(+) viruses and their functional roles.